ANALISIS MUTU GARAM PULAU NASI KECAMATAN PULAU ACEH KABUPATEN ACEH BESAR PROVINSI ACEH - T. Hadinia Nur Frastiwi; Anhar Rozi, S.Pi., M.Si (Universitas Teuku Umar, 2022)
Nasi Island in Pulau Aceh District is the westernmost island in Indonesia whose people have been producing salt since ancient times. The purpose of this study was to determine the organoleptic and chemical quality of salt produced by salt farmers on Nasi Island. The method used was descriptive method. The results of the organoleptic test on salt quality through duo trio difference test stated that there was a difference of 15 people, and this number had already met the minimum number of requirements for a significant difference of 5% level. The results of the chemical analysis of salt included the water content of the tested salt was 5.08% (SNI 01-3556-2000) and (SNI 01-4435-2000). The NaCl content in the tested salt was 8.33% (SNI 01-3556-2000). The level of iodine (KIO3) in the tested salt was 0.0114% (SNI 01-3556-2000). It can be concluded that the organoleptic test showed that the salt produced by Nasi Island salt farmers was significantly different from the comparison salt. In chemical analysis, the salt water content had met the requirements as industrial and consumption raw materials. Furthermore, the content of sodium chloride (NaCl) with iodine (KIO3) had not been fulfilled.Keywords : Chemical analysis, Organoleptic, Salt quality analysis.